Prevalence of vision impairment and refractive error in school children in Ba Ria – Vung Tau province, Vietnam. (28th January 2014) - Paudel, Prakash; Ramson, Prasidh; Naduvilath, Thomas; Wilson, David; Phuong, Ha Thanh; Ho, Suit M; Giap, Nguyen V
Abstract Background To assess the prevalence of vision impairment and refractive error in school children 12–15 years of age in Ba Ria – Vung Tau province, Vietnam. Design Prospective, cross‐sectional study. Participants 2238 secondary school children. Methods Subjects were selected based on stratified multistage cluster sampling of 13 secondary schools from urban, rural and semi‐urban areas. The examination included visual acuity measurements, ocular motility evaluation, cycloplegic autorefraction, and examination of the external eye, anterior segment, media and fundus. Main Outcome Measures Visual acuity and principal cause of vision impairment. Results The prevalence of uncorrected and presenting visual acuity ≤6/12 in the better eye were 19.4% (95% confidence interval, 12.5–26.3) and 12.2% (95% confidence interval, 8.8–15.6), respectively. Refractive error was the cause of vision impairment in 92.7%, amblyopia in 2.2%, cataract in 0.7%, retinal disorders in 0.4%, other causes in 1.5% and unexplained causes in the remaining 2.6%. The prevalence of vision impairment due to myopia in either eye (–0.50 diopter or greater) was 20.4% (95% confidence interval, 12.8–28.0), hyperopia (≥2.00 D) was 0.4% (95% confidence interval, 0.0–0.7) and emmetropia with astigmatism (≥0.75 D) was 0.7% (95% confidence interval, 0.2–1.2). Vision impairment due to myopia was associated with higher school grade and increased time spent reading and working on a computer. Conclusions Uncorrected refractive error, particularly myopia, among secondary school children in Vietnam is a major public health problem. School‐based eye health initiative such as refractive error screening is warranted to reduce vision impairment.